2015
DOI: 10.1001/jamaoncol.2015.2969
|View full text |Cite
|
Sign up to set email alerts
|

Resource Utilization and Safety of Outpatient Management Following Intensive Induction or Salvage Chemotherapy for Acute Myeloid Leukemia or Myelodysplastic Syndrome

Abstract: Importance Adults with acute myeloid leukemia (AML) typically remain hospitalized after induction or salvage chemotherapy until blood count recovery, with resulting prolonged inpatient stays being a primary driver of healthcare cost. Pilot studies suggest that outpatient management following chemotherapy might be safe and could reduce cost for these patients. Objective To compare safety, resource utilization, infections and cost between adults discharged early following AML induction or salvage chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
7
47
0
Order By: Relevance
“…In the study by Ruiz-Argüelles et al, the early discharge of AML patients following completion of induction chemotherapy led to an average savings of 1700 USD per patient [25]. Consistent with this estimate, we found approximate cost savings of 2000 USD charged per patient discharged early compared to inpatient controls in both the pilot and phase 2 studies conducted at the UW/SCCA [27,28]. Efforts to quantify fiscal gains from changes in clinical practice are often hindered by the inherent difficulties in calculating healthcare costs, particularly in the U.S. For example, we utilized hospital “charges” as a surrogate for healthcare cost in our studies.…”
Section: Potential Benefits Of Outpatient Managementsupporting
confidence: 86%
See 2 more Smart Citations
“…In the study by Ruiz-Argüelles et al, the early discharge of AML patients following completion of induction chemotherapy led to an average savings of 1700 USD per patient [25]. Consistent with this estimate, we found approximate cost savings of 2000 USD charged per patient discharged early compared to inpatient controls in both the pilot and phase 2 studies conducted at the UW/SCCA [27,28]. Efforts to quantify fiscal gains from changes in clinical practice are often hindered by the inherent difficulties in calculating healthcare costs, particularly in the U.S. For example, we utilized hospital “charges” as a surrogate for healthcare cost in our studies.…”
Section: Potential Benefits Of Outpatient Managementsupporting
confidence: 86%
“…Based on the data obtained in our pilot study, we then conducted a larger, comparative, non-randomized phase 2 prospective study, in which we enrolled 178 adults AML or high-risk MDS patients after receipt of induction or re-induction chemotherapy [28]. Within 72 h of chemotherapy completion, patients were reassessed medically and deemed eligible for early discharge if they had an ECOG performance status of 0–1, bilirubin level less than or equal to 3 times the upper limit of normal, glomerular filtration rate at least 25% of the lower limit of normal, and no clinical signs of heart failure or bleeding.…”
Section: Previous Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm the findings of earlier studies, which showed that outpatient high-dose chemotherapy and autologous stem cell transplantation are efficient, effective, and acceptable (114,115). More recently even, the challenge of shifting towards outpatient care has been raised for other cancers, also with favourable outcomes: the treatment by vincristine, dactinomycin, and cyclophosphamide for children with solid tumours, as outpatient instead of the traditional twoday inpatient stay, has proven safe, cheaper, and more satisfactory for the patient (116); outpatient delivery of chemotherapy for acute lymphoblastic leukaemia/ lymphoma was safe and not associated with increased toxicity as compared to inpatient delivery (117); outpatient management after chemotherapy for adults with acute myeloid leukaemia or myelodysplastic syndrome reduced costs and use of IV antibiotics (118). In other terms, the administration of chemotherapy in outpatient settings produces comparable outcomes while increasing patients' satisfaction and reducing costs.…”
Section: Evolution Of Cancer Care Unitsmentioning
confidence: 99%
“…Recent data suggest this is unnecessary if, as outpatients, patients reside close to a hospital, have a caregiver readily available, and are prepared to visit a dedicated outpatient facility several times weekly [122]. Similarly, randomized data suggest no value in a diet free of fresh fruits and vegetables ("a neutropenic diet") [123].…”
Section: Supportive Care Issuesmentioning
confidence: 99%